Use of Haddenham Venex armsleeve for lymphoedema management in clinical practice. (1st October 2019) - Everett, Jeanne; Lawrance, Sue
Abstract : Lymphoedema of the upper limb can be an unwelcome side effect of treatment for breast cancer, some skin cancers, as well as having non-cancer-related causes. Treatment focuses on patient self-management, and involves skin care, exercise, lymphatic drainage massage and compression. Lymphoedema is a chronic, life-long condition, and the correct choice of garment will influence treatment outcomes, enhancing concordance and improving quality of life. This article examines how, following recent improvements to the comfort and overall fit of the Haddenham Venex lymphoedema sleeve, patient feedback informed the implementation of further modifications, and how gaining feedback from patients has empowered them to manage and monitor their own condition. By taking ownership for their own care, long-term control of the condition is improved and self-management is enhanced.